Yarkovsky effect: Delivery of Asteroids to near earth orbits - Mohamed, Rafa; Alhasi, Awad (Libyan Journal of Science &Technology, 2022)
Significant advances have been made in recent years and extensive studies are going for assisting the asteroids’ destiny. From these studies, we hope to obtain a much better understanding of the influence of the non-gravitational forces on the asteroids, and the overall history of the solar system. At the same time, Yarkovsky effect is important in terms of impact hazard. Both the pure scientific concerns, and the impact hazardous point of view concentrated on the need of developing reliable plans of impact evidence, require a major struggle in order to improve the current knowledge of the size of the Yarkovsky affection on these objects. In this article, a brief description of Yarkovsky effect is presented, and the delivery of NEAs to near Earth orbits as well.